Ion is a genius! (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article offers a framework in the interplay of ancient and modern traditions of thought on art by juxtaposing Plato's notions of techné and inspiration, as developed in his dialogue Ion, with Immanuel Kant's concepts of rules and genius, as articulated in his seminal work Critique of the Power of Judgment. Building upon these ideas, these writings seek to speculate on the potential for artistic practice to engage meaningfully with the theoretical underpinnings derived from philosophical inquiry.
Keywords: theater; theory; practice; concepts; inspiration